Solasodine accumulation in regenerated plants of Solanum torvum Sw Acúmulo de solasodina em plantas micropropagadas de Solanum torvum Sw - C.B Moreira; S.S Lima; M.A Esquibel; A Sato (Universidade Estadual Paulista, 2010)
A nodal segment culture was developed in order to assess Solanum torvum Sw. regeneration and solasodine levels. The influence of auxins (indoleacetic acid, 1-Naphthaleneacetic acid) and benzyl adenine on S. torvum growth in micropropagation was investigated. A nodal segment culture was initiated with seeds germinated in MS basal medium added of GA3 and grown in different concentrations of IAA, IAA + BAP and NAA + BAP. Sixty-day-old plants from the in vitro culture were collected, frozen and lyophilized; then, the methyl orange method was used to quantify solasodine for the spectrophotometric assay. The best results regarding plant regeneration and solasodine accumulation were obtained by using the MS basal medium without addition of plant growth regulators; however, there was great production of calluses presenting friable bases. Based on these results, cell cultures can be initiated from such calluses with application of other auxins and cytokinins to enhance solasodine production, besides different elicitors, light intensities and sucrose concentrations. A regeneração de Solanum torvum e a avaliação do conteúdo de solasodina foram os objetivos de cultura de segmentos nodais. A influência de auxinas (ácido 3-indolacético, ácido naftalenoacético) e de 6-benzilaminopurina no crescimento de S. torvum na micropropagação foi investigado. Cultura de segmentos nodais foi iniciada por sementes germinadas em meio básico MS acrescido de GA3 e cultivadas em diferentes concentrações de AIA, AIA + BAP e ANA + BAP. Plantas da cultura in vitro com 60 dias foram coletadas, congeladas e liofilizadas e o método de alaranjado de metila foi utilizado para quantificação de solasodina para o ensaio espectrofotométrico. Os melhores resultados para regeneração vegetal e acúmulo de solasodina foram alcançados no meio MS sem adição de reguladores de crescimento havendo, porém grande produção de calos de base friáveis. Esses resultados mostram que a partir desses calos, cultura de células pode ser iniciada com aplicação de outras auxinas e citocininas para o aumento da produção de solasodina além de diferentes eliciadores, intensidades luminosas e concentrações de sacarose.